Gabriela Mistral's Letters to Doris Dana - Mistral, Gabriela, 1889-1957 (Book collections on Project MUSE., 2018)
These letters, published in Spanish in 2010 and now translated for the first time into English, provide insight into her work as a poet and illuminate her perspectives on politics, especially war and human rights.